Aktualisasi Teori Herzberg: Suatu Kajian terhadap Kepuasan Kerja dan Kinerja Manajer Operasional (Penelitian di Perusahaan Kecil Rokok Sigaret Kretek Tangan di Wilayah Malang) - Noermijati, Noermijati (Jurnal Aplikasi Manajemen, 2008)
This research discusses about the actualization of Herzberg two-factor theory and job satisfaction and performance of operational managers in small Sigaret Kretek Tangan (SKT) companies in Malang Region. The research is examining whether the theory is applicable for operational managers in small SKT cigarette manufacturing company: Then it also examines the effect of job satisfaction on job performance and the effect of job performance on job satisfaction of operational managers. The operational manager's job performance is observed from the spiritual job performance side, using spiritual ability as its indicator The research is using factor analysis and structural equation modeling (SEM) method to answer the problems on Herzberg theory actualization and the pattern of variables relations. The research sample includes 157 operational managers from 47 small SKT cigarette manufacturing companies in Malang region. To complete the quantitative analysis, open questionnaire and interviews to several respondents were also used. The research result shows that Herzberg two-factor theory cannot be fully actualized for operational managers in small SKT cigarette manufacturing company in Malang region. Motivator and hygiene variable affecting respondents' job satisfaction. The research result analysis shows that motivator variable affects to job satisfaction, and also affects directly and indirectly to job performance through job satisfaction of operational managers. Hygiene variable affects to the emerge of job satisfaction, but hygiene variable doesn't have direct effect on job performance. However, hygiene variable actually has an indirect effect to job performance through job satisfaction and motivator variable. To the respondents, the job satisfaction that they feel in fact affects their job performance. The research result also shows that operational managers 'job performance affects their job satisfaction in a negative significant way. To the respondent, they work not only for material matters, but there is also other objective, they work as a fulfillment of self actualization. By working, they can do something useful for others. Working is a part of devoting to God implementation.